Faktor-Faktor yang Menyebabkan Obesitas Berisiko pada Mahasiswa Matematika FMIPA UNP Menggunakan Analisis Faktor - Siska Novita Sari; Helma Helma; Muhammad Subhan (Journal of Mathematics UNP, 2021)
Abstract - Obesity is a disorder characterized by the accumulation of fat tissue in the body excessively. Obesity can happen to anyone, including students. Many impacts of diseases that can attack is coronary heart disease, diabetes mellitus, hypertension and other dangerous diseases. Objectives for the review identify factors causing obesity. This research is done student of  studies program mathematics Faculty of Mathematics and Science (FMIPA) Department State University of Padang (UNP), data was collected through questionnaires deplopment with respondents as many 32 people were processed using factor analyze. From the analyze of the data can be obtained five new factors.Keywords - Factor analyze, Obesity, the impact of obesity diseaseAbstract-Obesity is a disorder characterized by the accumulation of fat tissue in the body excessively. Obesity can happen to anyone, including students. Many impacts of diseases that can attack is coronary heart disease, diabetes mellitus, hypertension and other dangerous diseases. Objectives for the review identify factors causing obesity. This research is done student of  studies program mathematics Faculty of Mathematics and Science (FMIPA) Department State University of Padang (UNP),data was collected through questionnaires deplopment with respondents as many 32 people were processed using factor analyze. From the analyze of the data can be obtained five new factors. Keywords- Factor analyze, Obesity, the impact of obesity disease